Perception of Sex and its Influence on Reproductive Sexual Behaviour Among Young Adolescents in Poor Urban Communities in Accra - Klu, D. (University of Ghana, 2013)
The study investigated the relationship between perception of sex and sexual behaviour among adolescents in poor urban communities in Accra. It also critically examined the attitudes of young adults towards sexual issues. The study further sought to investigate other sexual experiences of the adolescents in Ga-Mashie-a poor urban community in Accra. Round two survey of the EDULINK Urban Health and Poverty Project-individual questionnaire was used. The sample size was a total of 326 adolescents aged 15-24 which included 179 females and 147 males were used for the study. Out of this 326, 214(65.6%) perceived sex as not a form of monetary exchange, 29(8.9%) of them perceived sex as exchange for money and 83 (25.5%) did not share neither of the two perceptions. As far as perception of sex as morally wrong was concerned, 158(48.5%) perceived sex as morally right to engage in, 142(43.6%) of the respondents perceived sex as morally wrong and 26(8%) did not share neither of the two perception. On their knowledge of risk of getting infected with HIV/AIDS, about 60 per cent of the respondents thought they were at no risk of getting infected with HIV and the rest 40 per cent thought they have small, moderate and great risk of getting HIV. On their sexual behaviour measured by number of partners, 164(50.3%) had no sexual partner in the last 12 months, 124 (38%) had only one sexual partner and 38(11.7%) had two or more sexual partners. Again, about 42 per cent of the respondents reported to have watched both pornographic film and watched television where sexual issues were being discussed. Other control variables that were significant in predicting adolescents’ sexual behaviour were age, sex, media and their marital status. The results of the multinomial logistic regression on number of sexual partners indicated that perception of sex as form of monetary exchange and as morally wrong were significant predictors of adolescents’ sexual behaviour. However, this was more significant with the addition of the intermediate variable thus through their knowledge of risk of getting infected with HIV/AIDS. Most adolescents (65.6%) in poor urban communities did not perceived sex as exchange for money or gifts and did not perceived sex as morally wrong hence their indulgence in risky sexual behaviour such as taking of multiple sexual partners. It is against this background that education needs to be intensified to change the perception of adolescents on sex and its related issues. Again, strengthening community structures through non-governmental organizations and opinion leaders to assist young people in these communities to make good/healthy sexual and reproductive health decision is another relevant recommendation.
Thesis (MA)-University of Ghana, 2013